Adverse events associated with home blood transfusion: A retrospective cohort study. Issue 11 (17th March 2021) - Sharp, Rebecca; Turner, Lisa; Altschwager, Jodie; Corsini, Nadia; Esterman, Adrian
Abstract: Aims and objectives: To determine the rate of individual and system adverse events associated with blood transfusion at home. Background: Home or residential care facility based blood transfusion is beneficial for individuals requiring transfusion due to reduced disruption to daily life and the comfort of a familiar environment. However, blood transfusion may result in serious adverse events. There is a lack of research in this area, and there is a need to identify rates of adverse events and evaluate the system used for this service. Design: Retrospective cohort study. Methods: Existing data routinely collected for clinical care were used to determine client and system adverse events of medically stable adults with a chronic disease who underwent blood transfusion in a home setting provided by a nurse‐led service. A STROBE EQUATOR checklist was used for this study (see Appendix S1 ). Results: There were 1790 episodes of care involving 533 participants, with 13 cases of transfusion reaction (incident rate [IR] 0.7%; 95% CI 0.43–1.25). Only five of these were severe, resulting in the cessation of the blood transfusion and further medical review or hospital admission (IR 0.28%; 95% CI 0.12–0.68). There were no cases of tampered blood packaging, expired or visually damaged blood products. There were 10 cases of incorrect paperwork (0.6%) and nine cases of incorrect temperature (0.5%). There were 153 cases of vascular access device adverse events (IR 8.5% 95% CI 7.3–9.9), most commonly, difficulty cannulating the individual ( n  = 82, 54%). Conclusions: A nurse‐led home blood transfusion service was associated with low rates of both individual and system adverse events. Further research is needed to explore the perception of those using this service and supports required to improve the experience. Relevance to clinical practice: Blood transfusions may be associated with increased risk of morbidity and mortality. This risk may be increased in a home setting due to the distance from an acute care facility. This study has demonstrated that a nurse‐led home blood transfusion service is safe (<1% adverse event rate) for those with a medically stable, chronic condition. There were few failures in the system used to provide this service. Adverse events associated with the vascular access device were the most common complication and the reason for most blood product wastage. Mainly, this was due to difficulty inserting the short‐term peripheral intravenous catheter (PIVC). RNs should consider ultrasound to aid PIVC insertion to facilitate treatment provision and enhance the experience of the individual.